The Effect of ESG Risk Rating on Corporate Profitability: The Role of Firm Size and Leverage as Moderating Variables - Syurmita Syurmita; Syahfitri Suryaningsi Welkom; Khansa Chikita Rayesha (Journal of Business, Social and Technology, 2026)
Background: Sustainalytics ESG Risk Rating has been identified as a determinant of corporate financial performance. However, its effect on profitability—particularly for developing markets like Indonesia—remains underexplored. This study examines how ESG risk relates to profitability and whether firm size or leverage moderates their relationship. Objective: This study seeks to determine the influence of ESG risk on profitability, with firm size and leverage as moderating variables. Methods: A quantitative study employing Moderated Regression Analysis (MRA) was conducted using 76 firms listed on the Indonesia Stock Exchange (IDX) in 2024. The proxy for profitability was Net Profit Margin (NPM), and ESG Risk Ratings were obtained from Sustainalytics. Results: ESG Risk Ratings negatively affect profitability (B = −2.418; p = 0.005), whereby higher sustainability risk impairs net profit margins. This negative effect is moderated by firm size (B = 0.094; p = 0.001), as larger firms are better equipped to manage ESG risks. Conversely, higher leverage strengthens the negative effect of ESG risk on profitability (B = −0.839; p = 0.001), as highly leveraged firms are less capable of addressing sustainability pressures. Conclusion: The results underscore the need for both ESG risk disclosure and governance. Larger firms cope with ESG risk more effectively than highly leveraged firms. Further research is warranted with a longer observation period and additional measures of profitability.